The Impact of Aerobic Activity Programs on Quality of Life and Cardiovascular Fitness in the Elderly: A Review - Agung Wahyu Permadi; Tanjung Subrata (Warmadewa University, 2025)
Aerobic activity is a gradual and targeted activity designed to enhance the body's ability to utilize cardiac and respiratory capacity (oxygen) effectively in the elderly. The growing number of elderly people and their long-term effects on psychological factors affecting their quality of life. This review aims to evaluate and synthesize scientific evidence on the effects of aerobic activity programs on quality of life and cardiovascular fitness in the elderly. This analysis uses the Preferred Reporting for Systematic Review and Meta-analysis (PRISMA) method. A systematic search was conducted by searching the Cochrane Database of Systematic Reviews, Embase, and Pubmed, independently using the terms